Identification of gelsemine metabolites in rat liver S9 by high‐performance liquid chromatography/quadrupole‐time‐of‐flight mass spectrometry. (23rd November 2017) - Yang, Kun; Huang, Ya‐Jun; Xiao, Sa; Liu, Yan‐Chun; Sun, Zhi‐Liang; Liu, Yi‐Song; Tang, Qi; Liu, Zhao‐Ying
Abstract : Rationale: Gelsemine has been extensively studied because of its anti‐tumor, immunomodulatory, insecticidal itching and other significant effects. However, limited information on the pharmacokinetics and metabolism of gelsemine has been reported. Therefore, the purpose of the present study was to investigate the in vitro metabolism of gelsemine in rat liver S9 by using rapid and accurate high‐performance liquid chromatography/ quadrupole‐time‐of‐flight mass spectrometry (HPLC/QqTOF‐MS). Methods: The incubation mixture was processed with 15% trichloroacetic acid. Multiple scans of gelsemine metabolites and accurate mass measurements were automatically performed simultaneously through data‐dependent acquisition in only 30 min. The structural elucidations of these metabolites were performed by comparing their changes in accurate molecular masses and product ions with those of the parent drug. Results: Five metabolites of gelsemine were identified in rat liver S9. Of these, four metabolites of gelsemine were identified for the first time. The present results showed that the metabolic pathways of gelsemine are oxidation, demethylation, and dehydrogenation in rat liver S9. Conclusions: In this study, metabolites of gelsemine in liver S9 were identified and elucidated firstly using the HPLC/QqTOF‐MS method. The proposed metabolic pathways of gelsemine in liver S9 will provide a basis for further studies of the in vivo metabolism of gelsemine in animals and humans.